2021
DOI: 10.3389/fcvm.2021.724942
|View full text |Cite
|
Sign up to set email alerts
|

Early Coagulation Disorder Is Associated With an Increased Risk of Atrial Fibrillation in Septic Patients

Abstract: Background: Atrial fibrillation (AF) and coagulation disorder, two common complications of sepsis, are associated with the mortality. However, the relationship between early coagulation disorder and AF in sepsis remains elusive. This study aimed to evaluate the interaction between AF and early coagulation disorder on mortality.Methods: In this retrospective study, all data were extracted from the Medical Information Mart for Intensive Care III (MIMIC-III) database. Septic patients with coagulation tests during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Non-AF ischemic stroke was also observed to be related to hazard elements such as gender (male), high BMI, and smoking, which is consistent with preceding findings [31]. In addition, TnI, D-dimer, aPTT, and INR degrees have been higher within the AF organization, that is, regular with preceding studies, as coagulation problems are associated with an excessive hazard of AF [32,33].…”
Section: Discussionsupporting
confidence: 87%
“…Non-AF ischemic stroke was also observed to be related to hazard elements such as gender (male), high BMI, and smoking, which is consistent with preceding findings [31]. In addition, TnI, D-dimer, aPTT, and INR degrees have been higher within the AF organization, that is, regular with preceding studies, as coagulation problems are associated with an excessive hazard of AF [32,33].…”
Section: Discussionsupporting
confidence: 87%
“…The present study was a single-center, retrospective cohort study to assess the association between coagulation disorder score and the risk of adverse outcomes in critically ill patients with CHF. The coagulation disorder score was defined by platelet count, INR, and APTT with reference to the sepsisinduced coagulopathy (SIC) score and coagulopathy according to previous studies (Table 2) (18). The optimal cutoff was determined using X-tile software (Yale University, New Haven, CT) (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…On this basis, Long et al reported a composite coagulation disorder score with reference to SIC score and coagulopathy to evaluate early coagulation dysfunction, which combines the platelet count, INR and activated partial thromboplastin time (APTT). This score could effectively predict the risk of atrial fibrillation in patients with sepsis, which is associated with the 90-day mortality of patients (18). The major pathways that contribute to DIC include platelet and inflammatory cell activation and endothelial damage, which are the major hallmarks of heart failure (19).…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis-associated coagulopathy consists of a prolonged INR and a reduced platelet count, which was related to 28-day mortality in septic patients and was one way to assess disease severity ( 43 , 44 ). In a retrospective study of sepsis, coagulopathy within 24 h of admission was an independent risk factor for AF, with an INR of 1.5 (95%CI, 1.2–2.2) in the AF group ( 45 ). The INR was 1.46 (95%CI, 1.20–3.26) in this study, consistent with the above findings.…”
Section: Discussionmentioning
confidence: 99%